Billboard Media as Public Communication for Mudik Gratis Participation: Media Billboard sebagai Sarana Komunikasi Publik untuk Partisipasi dalam Program Mudik Gratis - Wicaksono, Hendra Setia Budi; Abadi , Totok Wahyu (House of Wisdom: Journal on Library and Information Sciences, 2025)
General Background: Public communication plays a vital role in disseminating government programs to citizens, particularly in campaigns that promote social participation. Specific Background: The East Java Provincial Transportation Agency utilized billboard media to inform the public about the 2023 “Mudik Gratis” (Free Homecoming) program, aiming to ensure safety and accessibility during the annual exodus period. Knowledge Gap: Despite technological advancements and the proliferation of digital media, the continued relevance and effectiveness of traditional billboards in influencing public behavior remain underexplored. Aims: This study investigates the effectiveness of billboards as a medium of public communication in enhancing community participation in the “Mudik Gratis 2023” program. Results: Using qualitative methods with purposive sampling of respondents aged 17–30 years, findings reveal that billboards remain effective in conveying clear, persuasive messages, particularly to audiences less engaged with digital media. Respondents acknowledged that the content was easily understandable and increased their enthusiasm to participate. Novelty: The study highlights that traditional outdoor media maintain communicative power in the digital era when strategically designed and placed. Implications: These findings emphasize the importance of integrating traditional and digital communication strategies in public service campaigns to maximize outreach and citizen engagement. Highlights: Billboard media remains effective for public information dissemination in the digital era. Clear design and strategic placement enhance audience understanding and engagement. Integration of traditional and digital media strengthens government communication outreach. Keywords: Effectiveness, Billboard, Public Communication, Community Participation